(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The current research aims to develop reading fluency and technological acceptance among secondary school students through a program based on some artificial intelligence applications and educational game stimuli. To achieve the research objectives, the researcher followed an experimental approach, conducting the experiment on a research sample consisting of (34) Second year of secondary school. They represent a research group to identify the effectiveness of a program based on some artificial intelligence applications and educational game stimuli in developing reading fluency and technological acceptance among secondary school students. The measurement tools were (the reading fluency test, and the technological acceptance scale for secondary school students), and appropriate statistical processing methods were applied. The research results showed the effectiveness of a program based on some artificial intelligence applications and educational game stimuli in developing reading fluency and technological acceptance among secondary school students. The research concluded by presenting some recommendations and proposals to improve practical contributions to developing reading fluency and technological acceptance among secondary school students.